Development and social security system sustainability - Razvan-Dorin, Burz (Munich, 2012)
"In this paper we propose to investigate the link between economic development, social security system and the sustainability of the policies pursued by states. In doing so, we start from clarifying and summarizing the main ideas on the concepts of development and social security. Depending on the approach to social security (narrow or broad) and the developing status of the states (developed or developing) we propose a matrix of classification and analysis that can offer new perspectives on decisions about type of policy to be pursued by governments to ensure sustainable development and social security system sustainability."